The Ontogeny of the Motivation That Underlies In-Group Bias - Buttelmann, David; Böhm, Robert (Psychological Science, 2014)
Humans demonstrate a clear bias toward members of their own group over members of other groups in a variety of ways. It has been argued that the motivation underlying this in-group bias in adults may be favoritism toward one’s own group (in-group love), derogation of the out-group (out-group hate), or both. Although some studies have demonstrated in-group bias among children and infants, nothing is known about the underlying motivations of this bias. Using a novel game, we found that in-group love is already present in children of preschool age and can motivate in-group-biased behavior across childhood. In contrast, out-group hate develops only after a child’s sixth birthday and is a sufficient motivation for in-group-biased behavior from school age onward. These results help to better identify the motivation that underlies in-group-biased behavior in children.